Didactics and teaching with accessibility and affectivity in higher education - Corredor, Olga Lucía León; Calderón, Dora Inés; García-Martínez, Álvaro; Reis, Marcia [UNESP] (Association for Computing Machinery (ACM), 2016)
Didactics and teaching are important practices in higher education especially to increase success rates of students from normally excluded populations in university settings. In this article we analyse the ACACIA Project (561754-EPP-1-2015-1-CO-EPPKA2-CBHE-JP) and reflect on the experiences in the work package called Cultiva - one of the packages proposed innovative practices of inclusion. The challenge is to change traditional ways of looking at the dropout and failure of students, especially in teacher training in an organizational section named CADEP (Centro de Apoyo y Desarrollo Educativo y Profesional). In this paper, we present the changes made in the organizational development aspects of these traditional institutions with respect to how teachers are formed with respect to their personal, cognitive, interpretive, and practical skills. The focus of the analysis is the university education aiming that populations in marginal situations are not excluded from training processes for their vulnerability.
Keywords: Accessibility; Affectivity; Inclusive education; Learning; Technology and didactic; University teachers